1992
DOI: 10.1016/0378-1097(92)90270-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of fibronectin and fibronectin binding protein (FnBP) of Staphylococcus aureus with murine phagocytes and lymphocytes

Abstract: In the present study we examined the in vitro and in vivo interactions of a cloned staphylococcal fibronectin binding protein (FnBP) and plasma fibronectin (Fn) with polymorphonuclear cells (PMNs) and macrophages, and how antibodies against FnBP affect the phagocytosis process in vitro. Moreover, the interaction of FnBP and Fn coupled on latex beads as ‘artificial bacteria’ and ‘artificially opsonized bacteria’ with murine spleen cells and peritoneal macrophages was tested. The major finding of the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It has been reported that serum fibronectin (FN) induces the aggregation of S. aureus, and also affects the interaction between bacteria and polymorphonuclear leukocytes (5,24). Macrophages are important phagocytes that produce various kinds of chemical mediators such as superoxide anion, hydrogen peroxide and nitric oxide, and synthesize heat-shock proteins after the ingestion of S. aureus (4,(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that serum fibronectin (FN) induces the aggregation of S. aureus, and also affects the interaction between bacteria and polymorphonuclear leukocytes (5,24). Macrophages are important phagocytes that produce various kinds of chemical mediators such as superoxide anion, hydrogen peroxide and nitric oxide, and synthesize heat-shock proteins after the ingestion of S. aureus (4,(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…In mononuclear phagocytes the main receptor for fibronectin is an α5β1 integrin, also named VLA-5 (Ruoslahti 1991). The uptake of Staphylococcus aureus by murine peritoneal macrophages is mediated by a fibronectin-binding protein expressed in the bacteria surface and can be increased by addition of exogenous plasma fibronectin (Rozalska and Wadstrom 1992). The uptake of Staphylococcus aureus by murine peritoneal macrophages is mediated by a fibronectin-binding protein expressed in the bacteria surface and can be increased by addition of exogenous plasma fibronectin (Rozalska and Wadstrom 1992).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that rabbit polyclonal antibodies raised againsl two fibroncctin-binding proteins (gene fusion preparations i.e. gal-FnBP A and ZZ-FnBP A) of Staphylococcus aureus act as specific opsonins in vitro [11]. Bacteria preincubated wiih immune sera were ingested by mouse peritoneal macrophages more effectively than bacteria treated with preimmune serum.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were infected iniraperiloneally with i", aureu.i Cowan I (2 x 10'). Six and 24 h post infection, the number ofCFU in homogcnales of spleen and liver, and in Ihe peritoneal fluid was determined on blood agar as described previously [ 11 ], The results are expressed as mean ± SD for groups of six animals.…”
Section: Methodsmentioning
confidence: 99%